Adolescent Education in the Secondary School Research Analysis. Research Upgrading Guidelines - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2005)
The problem approached in the article is highly significant both theoretically and practically. It is the problem of opportunities for adolescent education upgrading in the secondary school. The article draws the line behind the vast research carried out in this area and registers the steady tendency of the reclining motivation in adolescent learning. The presence of impediments in the adolescent learning process is permanent. The aim of the research is to provide adolescent education upgrading guidelines on the basis of the research data obtained in 2002-2005 carried out on the auspices of the Ministry of Education and Science of the Republic of Lithuania. The object of research – analysis of the adolescent education in the secondary school upgrading opportunities. Research methods - literature review, empirical data analysis, model construction. In the concluding part the emphasis falls on the necessity to approach the problem in a complex and longitudinal study and on the interaction of the elements of the educational system with the results of education and on the analysis of the function in the learning reality.
Keywords: educational research; development opportunities; gifted children; children with special needs; delinquents